Enhanced biodegradation of trinitrotoluene in rhizosphere soil by native grasses - Li, Na; Yang, Kenny; Lin, Chungho; Yang, John (Frontiers in Environmental Science, 2024)
Soil contamination by the munition explosive residues of 2,4,6-trinitrotoluene (TNT) and its metabolites resulting primarily from military operations has beenwas identified as a threat to human health and ecosystems. TNT and its metabolites are persistent in the environment and toxic to human health. Conventional remediation methods of TNT-contaminated soils included incineration, composting, or bioslurry. However, The biodegradation by native plants thatto removes this hazardous compound or reduces its toxicity has is beingen considered as athe most cost-effective and environmental-sound approach for the cleanup orand restoration of TNT-contaminated sites soils, which is little reported. This study was aims to investigate the TNT biodegradation and kinetics by in two selected native grasses in the species-specific rhizosphere soils through growth chamber experiments. Native Eeastern gamma grass (Tripsacum dactyloides) and switchgrass (Panicum virgatum L.) were grown in the soil spiked with 14 C-TNT for 8 weeks. The 14 C-TNT mineralization ratesdegradation and degradativeon metabolite profiles in the rhizosphere soils were determined by liquid scintillation counter and high-performance liquid chromatography coupled with an online scintillation counter, respectively. Results indicated that both native grass species have significantly enhanced the 14 C-TNT mineralization or degradation in the rhizosphere soils as compared with the control rhizosphere soils. More than 95% of the applied 14 C-TNT was degraded in the first 7 days, and the rate then reached a steady state afterwards, but less than 10% of the TNT applied werewas completely mineralized and transformed into CO2. The degradative reactionon was found to follow second-order kinetics. Six major TNT degradative metabolites have been were detected and identified in the rhizosphere soils. Overall, switch grass appeared to be more effective for biodegrading TNT than eastern gamma grass. This study research demonstrated that the native grass species, especially switch grass, wouldcould have the potential to mitigate the adverse human health and ecologicalenvironmental risks of TNT-contaminated sites and canto be considered as an environmental-friend, sustainablesound remediation approach to safeguard the human health from the TNT contamination.